2023
DOI: 10.3390/pharmaceutics15020638
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Delivery of MIW815 (ADU-S100) for Potentiated STING Activation

Abstract: Stimulator of interferon genes (STING) agonists can improve the anticancer efficacy of immune checkpoint blockade by amplifying tumor immunogenicity. However, the clinical translation of cyclic dinucleotides (CDNs) as STING agonists is hindered by their poor drug-like properties. In this study, we investigated the design criteria for DOTAP/cholesterol liposomes for the systemic delivery of ADU-S100 and delineated the impact of key formulation factors on the loading efficiency, serum stability, and STING agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Optimization studies by Haghiralsadat et al found that the liposomal cationic lipid, DOTAP, in combination with stearoyl phosphoethanolamine-polyethylene glycol, produced stable round-shaped particles without the aggregate formation and an average diameter of 71 nm . DOTAP/cholesterol liposomes could also resist destabilizing effects from serum proteins. , The protein delivery efficiency of liposomal formulations would depend on the average diameter and the cellular uptake. Yan and Huang demonstrated that 20 μg of ovalbumin (OVA) formulated in 200 nmol DOTAP with a particle size range of 350–550 nm, protein loading capacity of 95–90%, and zeta potential of 29–38 mV had the best OVA-specific antibody response, suggesting both Th1 and Th2 immune responses were generated by this formulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization studies by Haghiralsadat et al found that the liposomal cationic lipid, DOTAP, in combination with stearoyl phosphoethanolamine-polyethylene glycol, produced stable round-shaped particles without the aggregate formation and an average diameter of 71 nm . DOTAP/cholesterol liposomes could also resist destabilizing effects from serum proteins. , The protein delivery efficiency of liposomal formulations would depend on the average diameter and the cellular uptake. Yan and Huang demonstrated that 20 μg of ovalbumin (OVA) formulated in 200 nmol DOTAP with a particle size range of 350–550 nm, protein loading capacity of 95–90%, and zeta potential of 29–38 mV had the best OVA-specific antibody response, suggesting both Th1 and Th2 immune responses were generated by this formulation .…”
Section: Discussionmentioning
confidence: 99%
“…43 DOTAP/cholesterol liposomes could also resist destabilizing effects from serum proteins. 44,45 The protein delivery efficiency of liposomal formulations would depend on the average diameter and the cellular uptake. Yan and Huang demonstrated that 20 μg of ovalbumin (OVA) formulated in 200 nmol DOTAP with a particle size range of 350−550 nm, protein loading capacity of 95−90%, and zeta potential of 29− 38 mV had the best OVA-specific antibody response, suggesting both Th1 and Th2 immune responses were generated by this formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of liposome composition allowed researchers to obtain CDNs stably incorporated into the liposomes, protect CDNs from spontaneous degradation in the blood, and retain the activity of ADU-100 [216], and diABZI [217] and various CDNs in extracellular vesicles [218]. Moreover, virus-like particles containing long DNA strands encapsulated in cationic liposomes showed some promise in inducing the liquid-phase condensation of cGAS, thereby activating STING [219].…”
Section: Nanosystems For Efficient Delivery Of Cgas-sting Modulatorsmentioning
confidence: 99%
“…Presently, ADU-S100 is undergoing phase I/II clinical trials for treating advanced metastatic solid tumors and lymphomas [ [26] , [27] , [28] ]. Nonetheless, ADU-S100 confronts several challenges, including issues related to stability, negative charge-associated impediments to effective cellular targeting, inefficient cytoplasmic transport, and heightened hydrophilicity [ 18 , 23 , [29] , [30] , [31] ]. Consequently, the predominant mode of ADU-S100 administration remains intratumoral delivery.…”
Section: Introductionmentioning
confidence: 99%